Christian Path to Mental Maturity: A Lucid Exposition of Christianity for the Multi-religious Classroom - Kariamadam, Jose (Journal of Dharma, 1999)
Antony Fernando, Christian Path to Mental Maturity. A Lucid Exposition of Christianity for the Multi-religious Classroom, Kadawata, Sri Lanka: 1998, pp.iii+262; $ 18.00; Ind.Rs.260.00 (ISBN 955-9036-13-0).